Physiological Performance of Laying Hens Undergoing Heat Stress and Fed Diets Containing Different Levels of Crude Artichoke (Cynara Carduncellus) and Mulberry (Morus alba L.) Leaf Powders, and Their Synergistic Mixture - Ali, Nashwan Majeed (American Journal of Botany and Bioengineering, 2025)
Adding medicinal plants to poultry diets is typically aimed at enhancing the birds’ health and physiological state, in addition to disease resistance. In this study, 144 Lohmann Brown laying hens at 23 weeks of age were randomly divided into six treatments (24 hens/treatment, with three replicates of eight hens/replicate). The six treatment groups were fed a standard diet supplemented with artichoke leaf powder, mulberry leaf powder, and a mixture of both, at the following ratios: 0, 1, 1.5, 1, 1.5, and 1.5+1.5 g/kg feed for each treatment, respectively. The following parameters were studied: cholesterol concentration, protein concentration, glucose concentration, calcium concentration, and phosphorus concentration. Blood was collected from the birds in each replicate every two weeks throughout the four-month study period, and the final average was calculated for each month. The results indicate that the synergistic mixture had a highly significant effect in improving the blood’s biochemical parameters, including cholesterol concentration, total protein concentration, glucose concentration, and calcium and phosphorus levels. It can be concluded from this study that the addition of raw artichoke leaf powder, mulberry leaf powder, and their mixture to the diets of laying hens led to a significant improvement in the overall physiological and cellular characteristics of the blood. Consequently, this supplement can be used in laying hen diets to improve their physiological performance.